Efeito das relações bióticas sobre o estabelecimento de macroalgas de ecossistemas lóticos tropicais: interação com microalgas e pressão por herbivoria - Tonetto, Aurélio Fajar [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The stream macroalgae have been considered, along with periphyton, bryophytes and macrophytes, one of the main primary producers in streams environments. For this reason, in recent decades many studies have been performed to understand the spatiotemporal distribution of these organisms. Most of these studies have only investigated the effects of environmental variables on patterns of ecological distribution of macroalgae streams. However, only the relationship between the occurrence and distribution of these organisms and the changes in environment has been shown to be poorly predictive in relation to the establishment and maintenance of macroalgae in these ecosystems. Thus, it seems clear that, beyond the dynamic mosaic of environmental conditions, other forces acting on these organisms should be considered in the analysis of their ecological distributions. In this sense, it is possible to imagine that biotic interactions on a small scale, that occur between coexistent organisms in the same stream stretch can also significantly influence on the ecological responses of these organisms. Microalgae and herbivorous, for example, are organisms that coexist intimately with macroalgae and therefore must have a relevant role in the distribution of these organisms in the environment. In fact, some studies have suggested that the internal factors of community seem to be more important in determining their variations than external, occasional or seasonal factors that act during the period of colonization. In this context, the present study investigated the possible existing biotic interactions between micro and macroalgae in tropical streams, by conducting an experimental study. More specifically, the first objective was to evaluate the existence of competition or cooperation between benthic algae (micro and macroalgae) over a process of colonization on artificial substrates. In addition, we tried to correlate these interactions with the dynamic ...

As macroalgas lóticas têm sido consideradas, juntamente com perifíton, briófitas e macrófitas, um dos principais produtores primários de ambientes de riachos. Por essa razão, nas últimas décadas muitos trabalhos vêm sendo realizados na tentativa de entender-se a distribuição espaço-temporal desses organismos. A grande maioria desses trabalhos tem investigado exclusivamente os efeitos de variáveis ambientais sobre os padrões de distribuição ecológica das macroalgas de riachos. Entretanto, apenas a relação entre a ocorrência e distribuição desses organismos e as variações do ambiente tem demostrado ser pouco preditiva em relação ao estabelecimento e manutenção das macroalgas nestes ecossistemas. Assim, parece claro que, além do mosaico dinâmico de condições ambientais, outras forças que atuam sobre estes organismos devem ser consideradas na análise de suas distribuições ecológicas. Neste sentido, é possível imaginar que as interações bióticas, em pequena escala, que ocorrem entre os organismos que coexistem em um mesmo trecho de riacho também possam interferir de maneira significativa nas respostas ecológias desses organismos. As microalgas e macro-invertebrados herbívoros, por exemplo, são organismos que coexistem intimamente com as macroalgas e, portanto, devem possuir papel relevante na distribuição desses organismos no ambiente. De fato, alguns estudos têm sugerido que os fatores internos de uma comunidade parecem ser mais importantes para determinar as suas variações do que os fatores externos, pontuais ou sazonais, que atuam durante o período de colonização. Neste contexto, o presente estudo investigou as possíveis interações bióticas existentes entre as micro e macroalgas de riachos tropicais, através da condução de um estudo experimental. De forma mais específica, o primeiro objetivo foi avaliar a existência de competitição ou cooperação entre as algas bentônicas (micro e...
Keywords: Algae; Alga; Microalga; Perifíton; Herbivoria